The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/pbi.12881
|View full text |Cite
|
Sign up to set email alerts
|

Establishing RNA virus resistance in plants by harnessing CRISPR immune system

Abstract: SummaryRecently, CRISPR‐Cas (clustered, regularly interspaced short palindromic repeats–CRISPR‐associated proteins) system has been used to produce plants resistant to DNA virus infections. However, there is no RNA virus control method in plants that uses CRISPR‐Cas system to target the viral genome directly. Here, we reprogrammed the CRISPR‐Cas9 system from Francisella novicida to confer molecular immunity against RNA viruses in Nicotiana benthamiana and Arabidopsis plants. Plants expressing FnCas9 and sgRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
100
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(117 citation statements)
references
References 35 publications
(57 reference statements)
1
100
0
1
Order By: Relevance
“…Previous studies harnessing CRISPR-Cas proteins, such as FnCas9 from Francisella novicia, to target RNA viruses have shown that the binding, but not the cleavage, ability of these proteins is sufficient to inhibit virus replication in mammalian and plant cells [45,49]. Our data show that the HEPN-dependent catalytic activity of CasRx is essential for efficient virus interference, which in turn indicate that the observed CasRxmediated virus interference results from targeted viral genomic degradation.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies harnessing CRISPR-Cas proteins, such as FnCas9 from Francisella novicia, to target RNA viruses have shown that the binding, but not the cleavage, ability of these proteins is sufficient to inhibit virus replication in mammalian and plant cells [45,49]. Our data show that the HEPN-dependent catalytic activity of CasRx is essential for efficient virus interference, which in turn indicate that the observed CasRxmediated virus interference results from targeted viral genomic degradation.…”
Section: Discussionsupporting
confidence: 56%
“…However, through long-term co-evolution, eukaryotic viruses have developed methods of antagonize RNAi, which limited the applications in agriculture. In recent years, the CRISPR/Cas9 machinery has been exploited to combat eukaryotic viruses in dicot plants (Ali et al, 2015;Aman et al, 2018;Baltes et al, 2015;Ji et al, 2015;Zhang et al, 2018). To our knowledge, this is the first report of a method targeting the viral RNA to control viral diseases in monocot plants.…”
mentioning
confidence: 97%
“…Dear Editor, Besides its powerful capability for genome editing, the clustered, regularly interspaced short palindromic repeats (CRISPR)/CRISPRassociated (Cas) (CRISPR/Cas) systems, has been exploited to combat virus infection in eukaryotic organisms (Zaidi et al, 2016). By harnessing CRISPR/Cas system, its compelling inhibiting activities against DNA viruses (Ali et al, 2015;Baltes et al, 2015;Ji et al, 2015) or RNA viruses (Aman et al, 2018;Zhang et al, 2018) were reported in many cases. Moreover, due to the facts that the eukaryotic viruses themselves do not equip the ability to counter this prokaryotic immune defense, by utilization of such strategy, we could establish effective control and eradiation strategy against the eukaryotic virus.…”
mentioning
confidence: 99%
See 2 more Smart Citations